2018
DOI: 10.1186/s12906-018-2341-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acupuncture on nutritional state of patients with stable chronic obstructive pulmonary disease (COPD): re-analysis of COPD acupuncture trial, a randomized controlled trial

Abstract: BackgroundThere are an increasing number of evidences that chronic obstructive pulmonary disease (COPD) is a systemic illness and that bodyweight loss is its prominent manifestation. We focused on the nutritional outcomes to find out the effectiveness of acupuncture on nutritional state of COPD patients and on their prognosis in our previous interventional study.MethodsThe present study is re-analysis of our previous interventional study, COPD Acupuncture Trial (CAT) published in 2012. Data from CAT was re-ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 39 publications
0
19
1
1
Order By: Relevance
“…The improvements in pulmonary functions and nutritional status observed in previous papers were not replicated in our study,13,25 although the same acupuncture points were used. However, we used a thinner needle (0.16 mm vs 0.35 mm) in this study because of the weak pain stimulus.…”
Section: Discussioncontrasting
confidence: 81%
“…The improvements in pulmonary functions and nutritional status observed in previous papers were not replicated in our study,13,25 although the same acupuncture points were used. However, we used a thinner needle (0.16 mm vs 0.35 mm) in this study because of the weak pain stimulus.…”
Section: Discussioncontrasting
confidence: 81%
“…Acupuncture improved peak oxygen uptake, peak minute ventilation, time to the limit of tolerance, and total SGRQ score of patients with COPD (44). Acupuncture also improved the nutritional state of patients with COPD, including body weight, respiratory muscle strength, nutritional hematological examination, and inflammatory biomarkers (6). According to the previous association rule analysis, ST36, BL12, and CV17 and ST36, BL12, and EXB1 could be considered the core acupoint combinations for the treatment of COPD (45).…”
Section: Discussionmentioning
confidence: 92%
“… 30 Previous researches have shown that acupuncture is an effective in the treatment of for COPD. 8 , 13 , 14 This overview provided a comprehensive mapping of the evidence on the effectiveness of acupuncture for COPD. A total of 9 SRs were included in this overview, the evaluation with AMSTAR 2 showed that the quality of included SRs was low or critically low and the results of the GRADE system evaluation showed that the strength of evidence was very low to low for most outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Proponents argue that acupuncture is effective at relieving symptoms and improving quality of life and activity endurance, and it is associated with fewer adverse effects than conventional approaches used to treat COPD. 11 In recent years, with the increasing number of clinical studies [12][13][14] on acupuncture treatment of COPD, a certain number of systematic reviews (SRs) [15][16][17][18][19][20][21][22][23] have been published to provide corresponding evidence supporting clinical decision-making. However, based on preliminary studies, the results of different systematic evaluations are not completely consistent, which are unable to effectively guide clinical practice.…”
Section: Introductionmentioning
confidence: 99%